Business intelligence use in planning and monitoring software development work - Kaisla, Karpalo (My University, 2021)
While the applications of business intelligence systems are diverse, their use in workload planning and monitoring especially in the software development context is a fairly unex-plored subject. Most research on business intelligence systems in general has focused on a managerial perspective as business intelligence tools are traditionally used in decision-support tasks. This thesis focused on exploring what affects software developers as IT pro-fessionals to accept business intelligence as part of the tools they use in their work in gen-eral and how these systems could be used in effective workload planning and monitoring tasks from the perspective of the software developers themselves. Software development is a suitable field to explore the use of business intelligence in workload planning and monitor-ing because of the diversity of tasks and project environment that is common in software development. The factors affecting business intelligence acceptance are to a large extent similar as the factors affecting the acceptance of new technologies in general: personal factors, technologi-cal factors, social factors and organizational factors usually play a role. Among software developers the most important seem to be technological and personal factors while social and organizational factors do not play a big role among software developers. Software developers recognized the importance of planning and monitoring their work at least on some level and found a business intelligence system to be a fairly suitable tool for this. Named advantages of a business intelligence system included for example visual and specifically designed interfaces, ability to analyze data, possibility to learn from the analyt-ics provided by the business intelligence system, time savings in weekly meetings and keep-ing up to date on the work situation of colleagues. The most notable disadvantage that was named was the current lack of real time connections to a source system as well as the extra time inputting data takes. As a whole, all the software developers agreed that a business intelligence system was a good option for planning and monitoring workloads and preferred it to using Excel spreadsheet
Keywords: Business intelligence, software development, workload planning, workload monitoring